The EU-funded EuropeanaTravel project - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
EuropeanaTravel is a targeted project for cultural content in the target area digital libraries of the eContentplus 2008 Work Programme funded by the European Commission. Its overall objective is to digitise content on the theme of travel and tourism for use in Europeana as requested by the EDL Foundation. The themed content will come from the wonderful collections of major university libraries and national libraries. The project is supported by CENL and LIBER, two founder members of the EDL Foundation, and by the Foundation itself. A secondary objective of the project is further to strengthen collaboration between CENL and LIBER by extending their experience of joint working, thus increasing human interoperability in support of Europeana. Other objectives include creating a LIBER closed access aggregation service to aggregate material from LIBER members for Europeana, continuing to mobilise support for Europeana amongst university libraries in a systematic way, and supporting the spread of best practice in digitisation by libraries. The consortium’s 19 members include 17 library members providing content from 16 countries drawn roughly equally from the membership of CENL and LIBER and from all European regions. The project will run for two years and work closely and flexibly with the Europeana team. The EuropeanaTravel project was launched in Tallinn on 11 May 2009 and this article has been compiled to celebrate that event.